DESIGNING AN ESP (ENGLISH FOR SPECIFIC PURPOSES) PROJECT FOR FLIGHT ATTENDANTS IN AVIATION IN UZBEKISTAN - Ergashev, Mirzokhidjon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article discusses the development of an English for Specific Purposes (ESP) program designed for pre-service flight attendants in Uzbekistan. The goal of this project is to help learners develop their communicative knowledge within the context of the aviation profession, with an emphasis on speaking and listening skills which are necessary to do the role of a steward or stewardess. A needs analysis was completed using both questionnaire surveys and in-flight observations which were recommended, so there would be an understanding of the learners’ linguistic and job needs. The course framework in this study is tied to a functional-notional syllabus which emphasizes the use of practical functions of language such as greeting passengers, making announcements, responding to emergencies and writing incident reports. Authentic material was used as functional examples of real-life communication in the form of video recordings, dialogues and the textbook English for Cabin Crew by Sue Ellis. Various formative and summative assessments such as role-plays, emergency announcements convention and a mock interview were used to assess learner development. This article identifies the need to align language teaching with the professional needs of the learners and illustrates how ESP pedagogy can spot the difference between learning in the classroom with actual communication needs in the workplace within the aviation context.